Retelling U.S. religious history - Tweed, Thomas A. (EBSCOhost eBook Collection, 1997)
I. Meaning and power at social sites Sexuality in American religious history Ann Taves -- Ritual sites in the narrative of American religion Tamar Frankiel -- Women's history is American religious history Ann Braude -- The Illusion of shifting demand: supply-side interpretations of American religious history Roger Finke -- II. Contract and exchange at geographical sites Eastward ho! American religion from the perspective of the Pacific rim Laurie F. Maffly-Kipp -- Indians, contact, and colonialism in the Deep South: themes for a postcolonial history of American religion Joel W. Martin -- Voices from the attic: the Canadian border and the writing of American religious history William Westfall -- Exchanging selves, exchanging souls: contact, combination, and American religious history Catherine L. Albanese